Drivers of and Solutions for the Overuse of Antidepressant Medication in Pediatric Populations - Cosgrove, Lisa; Morrill, Zenobia; Yusif, Michelangela; Vaswani, Akansha; Cathcart, Sadie; Troeger, Rebecca; Karter, Justin M. (Frontiers in Psychiatry, 2020)
Children in the United States and internationally are increasingly being diagnosed with depression and related psychiatric conditions and a recent study found that antidepressant (ADM) use in children and adolescents rose substantially in youth cohorts in five Western countries from 2005 to 2012 (Bachmann et al., 2016). However, there has been ongoing controversy over the effectiveness and safety of ADM use in children (Healy, 2019), including concerns about ADM increasing suicidality and self-harm. In addition to the increase in the diagnosis of depression, commercially driven off-label prescriptions have been cited as a significant reason for high rates of pediatric ADM prescribing. In this commentary, we discuss two drivers of the over-use of ADM, both of which are products of an increasingly medicalized approach to mental health: 1) the demand for mental health and depression screening in youth, despite the lack of evidence to support it, and 2) the renewed momentum of the Global Mental Health Movement and concomitant calls to ‘scale up’ the diagnosis and treatment of mental illness. Using the lens of institutional corruption, we identify the ways in which both guild and financial conflicts of interest create obstacles to rational prescribing practices in pediatric populations and offer suggestions for reform.